The Effectiveness of Using Powtoon-Based Learning Media on Learning Motivation and Listening Skills of Upper-Grade Students at UPT SD Negeri 2 Batu - Linayanti; Muhammad Hanafi; Rustam Efendy Rasyid (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to determine the effect of using PowToon learning media on improving elementary school students' learning motivation and listening skills compared to conventional learning methods. The study used a quasi-experimental design with two classes: a control class and an experimental class. The population and sample in this study were all 81 upper grade students divided into a control class of 29 students and an experimental class of 52 students. Data collection techniques in this study included tests, observations, questionnaires, and documentation. The data analysis technique used the IBM Statistics application with the N-Gain Score formula. The analysis results showed that the experimental class using PowToon experienced a significant improvement in listening learning outcomes with an average N-Gain score of 0.79 (79.80%), which is considered high. In contrast, the control class only achieved an average N-Gain of 0.18 (18.67%), which is in the low category. Student learning motivation in the experimental class also showed significantly better results, with 96% of students in the excellent category, compared to the control class, where the majority (87%) were in the poor category. Furthermore, students' listening skills in the experimental class improved significantly, as evidenced by observations and questionnaires that recorded increased activity, focus, and understanding of the material. The data also showed that PowToon media was able to create a more interactive and enjoyable learning environment, encouraging students to be more active in asking questions, discussing, and expressing their opinions. Overall, the results of this study indicate that the use of PowToon learning media is effective in significantly increasing students' learning motivation and listening skills compared to conventional learning methods. Therefore, PowToon is recommended as an alternative innovative learning medium in elementary schools to create more meaningful and enjoyable learning.